Akhlak Tasawuf Sebagai Pengembagan Kecerdasan Spiritual Mahasiswa - Sari, Susi Puspita; Mirdad, Jamal; Rina, Rina (Institut Agama Islam Sumatera Barat Pariaman, 2025)
Abstract Spiritual intelligence is one of the important aspects in the formation of students' character and personality in the modern era full of challenges. Sufism, as part of the Islamic teachings that emphasizes the purification of the heart and the approach to Allah, has a strategic role in forming a strong spiritual dimension. This research aims to examine the role of Sufism morality in developing students' spiritual intelligence. The method used is a literature study with a descriptive qualitative approach. The results of the study show that the values of Sufism such as sincerity, tawadhu', patience, zuhud, and muraqabah are able to form a calmer, wiser, and responsible student person, both in academic and social life. Sufism provides a solid moral and spiritual foundation, which is urgently needed in dealing with the moral crisis and value degradation that is rampant among the younger generation. Therefore, the integration of Sufism teachings in higher education is a strategic step in the holistic development of students' spiritual intelligence.